2017
DOI: 10.3892/mco.2017.1430
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous tubular and spindle cell carcinoma with a high nuclear grade and micropapillary pattern: A case report

Abstract: Mucinous tubular and spindle cell carcinoma (MTSCC) is rare in renal cell carcinoma (RCC) and usually demonstrates a low nuclear grade and a better prognosis compared with other RCCs. The authors present a case report of MTSCC containing an area of Fuhrman nuclear grade 3, in addition to an area with a micropapillary pattern. An 82-year-old man consulted a hospital due to macrohematuria, and a tumor in the right kidney was detected. The tumor was resected and histologically examined. The tumor consisted of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…The patient died a few months later. In another investigation, Sakatani et al ( 23 ) reported that the CT scan showed para-aortic lymph node metastasis and hepatic metastasis 5 months after radical nephrectomy. The patient received treatment with sunitinib but succumbed to a brain metastasis ( 23 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The patient died a few months later. In another investigation, Sakatani et al ( 23 ) reported that the CT scan showed para-aortic lymph node metastasis and hepatic metastasis 5 months after radical nephrectomy. The patient received treatment with sunitinib but succumbed to a brain metastasis ( 23 ).…”
Section: Discussionmentioning
confidence: 95%
“…In another investigation, Sakatani et al ( 23 ) reported that the CT scan showed para-aortic lymph node metastasis and hepatic metastasis 5 months after radical nephrectomy. The patient received treatment with sunitinib but succumbed to a brain metastasis ( 23 ). In a study by Shiro et al ( 24 ), distant metastases were revealed in the liver and bone by CT imaging after partial nephrectomy, and the patient, who received molecular targeted therapy and irradiation, succumbed due to tumor progression ( 24 ).…”
Section: Discussionmentioning
confidence: 95%
“…On an average of 8 months (range 1 to 19 months) follow-up, 5 (71%) patients developed metastatic disease, while 4 (57%) died of the disease. In 5 cases reported with epithelial high nuclear grade 15 , 18 , 20 , 21 , the mean patient age was 70 years (range 60 to 82 years), with all patients being male. With an average of 18 months (range 4 to 48 months) follow-up, 4 (80%) patients died from metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies in the literature suggest MTSCC to be non-aggressive, there have been sporadic reports of MTSCCs demonstrating high-grade features 13 22 and, occasionally, adverse clinical outcome 14 – 17 , 19 21 , 23 25 . Sarcomatoid transformation is the most well-established form of high grade transformation, with the tumor exhibiting a spindle cell component with marked nuclear pleomorphism, increased mitotic activity, frank tumor necrosis, and expansile growth 13 , 14 , 16 , 17 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, around 20 cases of recurrence after nephrectomy in RMTSCC have been reported. Among them, the detailed clinical course and prognosis after nephrectomy have been reported in 10 cases, which are summarized in Table . The median patient age was 67.5 (range 32–82) years.…”
Section: Discussionmentioning
confidence: 99%